Structural reforms and income distribution : new evidence for OECD countries - Wiese, Rasmus (2023)
This paper examines the impact of labour market and product market reforms on income inequality for 25 OECD countries, using the local projections approach and updates of the reform indicators put together by Duval et al. (2018) until 2020. Our results suggest that both types of (endogenized) reforms cause more income inequality. Consistent with this finding is that counter-reforms lead to less income inequality. However, the inequality-raising effects of reforms occur especially in countries that have below median levels of social spending; in countries where social spending is above the sample median, the effect of reform is mostly statistically insignificant.